2005
DOI: 10.1534/genetics.104.040410
|View full text |Cite
|
Sign up to set email alerts
|

On the Mutation Rate of Herpes Simplex Virus Type 1

Abstract: All seven DNA-based microbes for which carefully established mutation rates and mutational spectra were previously available displayed a genomic mutation rate in the neighborhood of 0.003 per chromosome replication. The pathogenic mammalian DNA virus herpes simplex type 1 has an estimated genomic mutation rate compatible with that value.A LL microbes with chromosomes composed of DNA, However, recently reported data can be used to fill this gap. The wild-type KOS strain of herpes simplex virus and for which bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 12 publications
4
54
0
1
Order By: Relevance
“…Third, the set of mesophiles that forms a basis for comparison have genomic mutation rates of 0.0025, 0.0027, 0.0027, 0.0030, 0.0038, 0.0040, 0.0045, and 0.0046 (mean ¼ 0.0035 6 0.00097) for Escherichia coli, S. cerevisiae, Herpes simplex virus 1, Neurospora crassa, bacteriophage l, bacteriophage T2/T4, Schizosaccharomyces pombe, and bacteriophage M13, respectively, estimated using the historical correction factor (Drake et al 1998;Fraser et al 2003;Drake and Hwang 2005). All but one of these values are based on only one or two reporter genes but the range of values resulting from the same methods of calculation is nevertheless less than twofold.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the set of mesophiles that forms a basis for comparison have genomic mutation rates of 0.0025, 0.0027, 0.0027, 0.0030, 0.0038, 0.0040, 0.0045, and 0.0046 (mean ¼ 0.0035 6 0.00097) for Escherichia coli, S. cerevisiae, Herpes simplex virus 1, Neurospora crassa, bacteriophage l, bacteriophage T2/T4, Schizosaccharomyces pombe, and bacteriophage M13, respectively, estimated using the historical correction factor (Drake et al 1998;Fraser et al 2003;Drake and Hwang 2005). All but one of these values are based on only one or two reporter genes but the range of values resulting from the same methods of calculation is nevertheless less than twofold.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the TK mutagenesis assay can detect less than 50% of all possible substitutions of tk mutations (Hwang, Liu, and Hwang, 2002). Despite this, an extensive study (Lu, Hwang, and Hwang, 2002a) of tk mutants derived from wild-type HSV-1 strain KOS found that HSV replicates DNA with a genomic mutation rate similar to those of other DNA-based microbes (Drake and Hwang, 2005). However, earlier studies (Hall et al, 1984;Hall et al, 1985;Parris and Harrington, 1982;Hwang and Chen, 1995) demonstrated a roughly 10-fold higher mutation frequency than those (Hwang et al, 1997;Lu, Hwang, and Hwang, 2002a) used to calculate the mutation rate.…”
Section: Antiviral Therapy and Emergence Of Resistant Mutantsmentioning
confidence: 99%
“…It is reasonable to predict that microorganisms also replicate under tight regulations to accomplish the required DNA replication fidelity for selection and fitness. This notion also applies to herpes simplex virus type 1 (HSV-1), which replicates DNA with a genomic mutation rate similar to those of other DNA-based microbes examined (Drake and Hwang, 2005). Since the HSV-1 genome can be easily manipulated, it offers a good model for a variety of studies, including the study of DNA replication (reviewed in (Coen, 1996)).…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of representative mutants then reveals a spectrum of mutation, which enables the efficiency of mutation detection and other parameters to be estimated. Such analyses have shown that all mesophilic micro-organisms examined (including DNA viruses) share two mutational characteristics: (i) the rates of mutation per genome fall near 0.003/replication, despite large differences in mutation rates per base pair (Drake 1991;Drake et al 1998;Drake and Hwang 2005), and (ii) $70% of the observed mutations are base-pair substitutions (BPSs) (Grogan et al 2001). However, extending this analysis to an archaeon from a geothermal environment revealed an apparently lower genomic rate (#0.0018) and a lower proportion of BPSs (33%) (Grogan et al 2001).…”
mentioning
confidence: 99%
“…rates display a genomic mutation rate of m g % 0.0034 (range 0.0025-0.0046)/chromosome replication (Drake 1991;Drake et al 1998;Drake and Hwang 2005). On the basis of an H. volcanii pyrE2 mutation rate of (1.93-5.87) 310 À8 and the coding sequence of 531 bp (including the termination codon), the midrange mutation rate per base pair is 7.34 3 10 À11 .…”
mentioning
confidence: 99%